Comparative study on combustion and oxy-fuel combustion environments using mixtures of coal with sugarcane bagasse and biomass sorghum bagasse by the thermogravimetric analysis - Galina, Natália Ribeiro; Romero Luna, Carlos M.; Arce, Gretta L.A.F.; Ávila, Ivonete (Elsevier, 2018)
Biomass and coal have different physicochemical properties and thermal behavior. During the co-combustion of coal-biomass mixtures, their thermal behavior varies according to the percentage of each fuel in the mixture. Thereby, this research aims to characterize the thermal behavior of mixtures of coal, sugarcane bagasse, and biomass sorghum bagasse as biomass in simulated combustion (O2/N2) and oxy-fuel combustion (O2/CO2) environments. Experiments have been performed in duplicate on a thermogravimetric analyzer at heating rate of 10 °C/min. A uniform granulometry was considered for all materials (63 μm) in order to ensure a homogeneous mixture. Four biomass percentages in the mixture (10, 25, 50 and 75%) have been studied. Based on thermogravimetric (TG) and thermogravimetric (DTG) analyses, parameters such as combustion index, synergism, and activation energy have been determined, as well as the combustion environment influence on these parameters. The results indicate that, although sugarcane bagasse has the lowest activation energy, the thermal behavior of both types of biomass is similar. Thus, biomass sorghum bagasse can be used as an alternative biomass to supply the power required during sugarcane off-season. For both mixtures, optimal results were obtained at 25% of biomass. By analyzing the environment influence on combustion behavior, the results indicate that when N2 is replaced with CO2, it is observed an increase in reaction reactivity, a higher oxidation rate of materials and an improvement in evaluated parameters.
Keywords: Biomass; Biomass sorghum; Coal; Sugarcane; TGA